Storage Container, Seed Moisture Level and Storage Condition Effects on Germination and Prevalence of Seed-Borne Fungi of Onion Seed (Global Journal of Science Frontier Research, 2018)
Laboratory experiments were conducted to evaluate the effects of storage containers (aluminum foil bag, polythene bag, plastic container, metal container and earthen pot), seed moisture level (5, 7, and 9%) and storage conditions (ambient temperature 30 ± 2o C, refrigerator 8 ± 1o C and dehumidified condition 20o C and RH at 40%) on germination and prevalence of seed-borne fungi of onion seed over a period of 170 days. Among the storage containers aluminum foil bag, polythene bag and plastic container performed better on germination and prevalence of seed-borne fungi of seeds. Seeds maintained high germination and lower seed-borne fungi when stored with 5 and 7% initial moisture. Considering storage conditions, refrigerator and dehumidified storage performed better. In two way interaction of container and seed moisture level, the highest germination and lowest seed-borne fungal infection was recorded in seeds stored in aluminum foil bag with 7% moisture content.
Keywords: storage container; seed moisture content; storage condition; germination; seed-borne fungi; onion seed